Draft Annual Plan, 1987-88 Volume I - Planning Commission (Planning Commission, 1987)
Although Bihar continues to be among the States with the lowest per capita income, the rate of growth of the State Domestic Product (SDP) has shown some significant increase from 1981-82, even if we ignore the very light growth rate of 11.27% in 1980-81 over that of the previous year i.e. 1979-80 which happened to be a year of severe drought with a low agricultural production base. the following figures show the annual growth rate from 1980-81 onwards
Planning Department Government of Bihar